Unicompartmental Knee Replacement Combined to Anterior Cruciate Ligament Reconstruction: Midterm Results - Ventura, Alberto; Legnani, Claudio; Terzaghi, Clara; Macchi, Vittorio; Borgo, Enrico (The Journal of Knee Surgery, 2019)
A study was conducted to retrospectively evaluate the outcomes of combined medial unicompartmental knee replacement (UKR) and anterior cruciate ligament (ACL) reconstruction. The hypothesis was that this procedure would lead to satisfying results in patients affected by medial osteoarthritis and ACL insufficiency. Fourteen patients with ACL deficiency and concomitant medial compartment symptomatic osteoarthritis were treated from 2006 to 2010. Twelve of them were followed-up for an average time of 7.8 year (range: 6–10 years). Assessment included Knee Osteoarthritis Outcome score (KOOS), Oxford Knee score (OKS), American Knee Society scores (AKSS), Western Ontario and McMaster (WOMAC) index of osteoarthritis, Tegner's activity level, objective examination including instrumented laxity test with KT-1000 arthrometer, and standard X-rays. KOOS score, OKS, WOMAC index, and the AKSS improved significantly at follow-up (p < 0.001). There was no clinical evidence of instability in any of the knees as evaluated with clinical and instrumented laxity testing (p < 0.001). No pathologic radiolucent lines were observed around the components. In one patient, a total knee prosthesis was implanted due to the progression of signs of osteoarthritis in the lateral compartment 3 years after primary surgery. UKR combined with ACL reconstruction is an effective therapeutic option for the treatment of combined medial unicompartmental knee osteoarthritis and ACL deficiency and confirms subjective and objective clinical improvement up to 8 years after surgery. This study reflects level IV evidence.
Keywords: unicompartmental knee replacement; medial osteoarthritis; anterior cruciate ligament; ACL reconstruction